Subcutaneous Fat Triacylglycerols Profile from Iberian Pigs as a Tool To Differentiate between Intensive and Extensive Fattening Systems - Gallardo, Emerenciana; Narváez-Rivas, Monica; Pablos, Fernando; Jurado, J. Marcos; León-Camacho, Manuel (Journal of Agricultural and Food Chemistry, 2012)
Triacylglycerols of subcutaneous fat of Iberian pigs reared on two different feeding systems, extensive and intensive, have been determined by gas chromatography with a flame ionization detector. Analyses were performed on a column coated with a bonded stationary phase (50% phenyl?50% methylpolysiloxane) with hydrogen as the carrier gas. Lipids were extracted by melting the subcutaneous fat in a microwave oven and then filtering and dissolving in hexane. A total amount of 1995 samples from several campaigns were considered. Palmitoyl-stearyl-oleoyl glycerol and palmitoyl-dioleoyl glycerol were the most abundant triacylglycerols found in the samples. A study on the discriminating power of the triacylglycerols to differentiate samples according to the pig feeding system was performed. By using the triacylglycerols as chemical descriptors, principal component analysis, linear discriminant analysis, and soft independent modeling of class analogy were applied. Dioleoyl-linoleoyl glycerol and oleoyl-dilinoleoyl glycerol were the most discriminating variables. Variable?variable plots of these two glycerols allow separation of the samples according to their content.
doi: 10.1021/jf2045312doi: 10.1021/jf2045312The following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: gas chromatography; iberian pig; pattern recognition; subcutaneous fat; triacylglycerols

Volatile composition and contribution to the aroma of Spanish honeydew honeys. Identification of a new chemical marker - Castro-Vazquez, L; Diaz-Maroto, M C; Perez-Coello, M S (JOURNAL OF AGRICULTURAL AND FOOD CHEMISTRY, 2006)
Honeydew honeys from holm-oak, oak, and forest were isolated for aroma compounds by simultaneous distillation-extraction and analyzed by gas chromatography-mass spectrometry. In all, 66 volatile components were identified and quantified. trans-Oak lactone, a characteristic volatile component of oak wood, is proposed as a new chemical marker for the plant origin of honeydew honeys. Other compounds, such as aminoacetophenone and propylanisol, could be considered characteristic of holm-oak honeydew honeys. A total of 15 volatile compounds presented odor activity values (OAVs) greater than 1, with phenylacetaldehyde and beta-damascenone being those with the highest OAVs.
Keywords: aroma; gas chromatography; honey; honeydew honey; volatile compounds

Suberin composition of reproduction cork from Quercus suber - García Vallejo, M C; Conde, E; Cadahía, E; DeSimon, B F (HOLZFORSCHUNG, 1997)
The monomeric composition of suberins from Spanish Quercus suber was determined by gas chromatography/mass spectrometry in the product of depolymerization of free extractives cork with sodium methoxide-methanol. 1-Alkanols (C-20-C-26)(1.8-6.4%), alkanoic acids (C-20-C-24)(2.2-8.1%), alpha,omega-alkanedioic acids (C-16-C-24)(6.1-10.2%) and omega-hydroxy-alkanoic acids (C-20-C-26, being C-22 and C-24 the most abundant)(28.7-37.3%) are identified. The erythro- and threo-9,10-dihydroxyoctadecanedioic (5.4-7.5%), erythro- and threo-9,10,18-trihydroxyoctadecanoic (7.6-11.8%), 9,10-epoxy-18-hydroxyoctadecanoic (1.2-3.1%) and 9,10-epoxy-octadecanodioic acids (1.0-4.4%) and the unsaturated 18-hydroxy-9-octadecenoic (8.1-11.5%) and 9-octadecenedioic (1.5-2.4%) acids are also important components. Ferulic acid (5.3-9.1%) is the main phenolic component of suberin. The studied samples differ in the relative proportion of the different monomers.
Keywords: Cork; epoxy acids; fatty alcohols; fatty and hydrixy-fatty acids; gas chromatography; gas chromatography/mass spectrometry; phenolics; Quercus suber; suberin